Use of the EFI score in endometriosis-associated infertility: A cost-effectiveness study. (October 2020) - Ferrier, Clément; Boujenah, Jérémy; Poncelet, Christophe; Chabbert-Buffet, Nathalie; Mathieu D'Argent, Emmanuelle; Carbillon, Lionel; Grynberg, Michael; Darai, Emile; Bendifallah, Sofiane
Highlights: After surgery, IVF-ICSI cycles induce more pregnancies than natural procreation attempts. IVF-ICSI were associated with susbstantial costs, compared to natural procreation. Supplementary pregnancies costs ranged from 20, 387 € to 59, 461 €. The EFI score is efficient in the decision between different care pathways after surgery. Abstract: Background: The management of endometriosis-related infertility is still under debate. The Endometriosis Fertility Index (EFI) score is performant to predict the occurrence of a spontaneous pregnancy following surgery, but was not evaluated in a cost-effectiveness perspective. Our objective was to quantify fertility outcomes, and costs of different care pathways for endometriosis-associated infertility after primary surgery, with a stratification on the EFI score. Study design: We conducted a cost-effectiveness analysis based on a decision-tree model in a Tertiary-care university hospital. Extracted form a prospectively maintained database, 608 patients with endometriosis-associated infertility, who underwent laparoscopic treatment with an evaluation of the EFI score, were discriminated between different strategies: natural conception, immediate IVF-ICSI, delayed IVF-ICSI. The pregnancy rate and the live birth rate were the effectiveness outcomes. We considered direct and indirect costs in each strategies. The analysis was stratified according to the EFI score. Results: After surgery, 163 women with immediate IVF-ICSI (strategy I) were compared with 445 women who had natural conception attempts during a year (strategy II). After a year failure of natural conception attempts, 133 women continuing natural conception attempts (strategy III) were compared with 168 women who had delayed IVF-ICSI (strategy IV). The respective PR and LBR were 62.6 % and 52.1 % for strategy I, and 32.4 % and 23.8 % for strategy II. Compared to strategy II, strategy I was more costly and more effective (Incremental Cost Effectiveness Ratio (ICER): 31, 469 €/pregnancy and 33, 568 €/live birth)). No added benefit was observed for patients in strategy I with an EFI score [0−3] after two IVF-ICSI cycles. Strategy III was strongly dominant versus strategy IV for patients with an EFI score [9–10]. Compared to strategy III, strategy VI was more costly and more effective (ICER: 79, 674 €/pregnancy, 53, 188 €/pregnancy and 27, 748 €/pregnancy respectively for patients with an EFI score [7–8], [4–6] and [0−3]). Conclusion: Immediate IVF-ICSI after surgery is effective but associated with substantial costs for the healthcare system. Taking into account healthcare costs, the EFI is a useful score for helping a couple decide between different care pathways –natural conception, immediate or delayed IVF-ICSI– after surgery for endometriosis-associated infertility.